PENGARUH PEMBELAJARAN PROBLEM SOLVING TERHADAP KETERAMPILAN PEMECAHAN MASALAH SISWA SMP - Muhammad Muslim; Rahmat Yunus; Arif Sholahuddin (Journal of Banua Science Education, 2022)
Learning generally still takes place traditionally with teacher-centered characteristics, using an expository approach so that the teacher dominates the process of learning activities in the class-room while the students are passive. Problem solving learning model is expected to be able to solve these problems. The research method uses a quasi-experimental model (quasi-experimental) with a "non-equivalent control group design" design. The research sample was taken from SMPN 5 Banjarmasin with a total of 183 students taken randomly and divided into two classes, the con-trol class and the experimental group. The results showed that the problem-solving model was able to improve student learning outcomes at SMPN 5 Banjarmasin based on the Gain value of 0.64 which was in the medium category increase. Through data analysis that meets the prerequi-site test this model is also able to improve students' problem-solving skills with an average in-crease of 82.58 with a significance test result of 0.029 meaning that there is a significant effect on the application of the problem-solving model with high significance.Keywords: Problem solving models, problem solving skills, junior high school students.ABSTRAKPembelajaran umumnya masih berlangsung secara tradisional dengan karakteristik berpusat pada guru, menggunakan pendekatan yang bersifat ekspositori sehingga guru lebih mendominasi proses aktivitas pembelajaran di kelas. Oleh karena itu, penggunaan model pembelajaran problem solving diharapkan mampu untuk memecahkan permasalahan tersebut. Metode penelitian menggunakan model quasi experiment dengan desain non-equivalent control group design. Sampel penelitian diambil dari SMPN 5 kota Banjarmasin dengan total 183 siswa yang diambil secara acak dan dibagi menjadi dua kelas sebagai kelas kontrol dan eksperimen. Hasil penelitian menunjukan model problem solving telah mampu meningkatkan hasil belajar siswa SMPN 5 Banjarmasin berdasarkan nilai gain 0,64 yang berada dalam peningkatan kategori sedang. Melalui analisis data yang memenuhi uji prasyarat model ini juga mampu meningkatkan keterampilan pemecahan masalah siswa dengan peningkatan rata-rata sebesar 82,58 dengan hasil uji signifikansi sebesar 0,029 yang berarti ada pengaruh yang signifikan pada penerapan model problem solving dengan siginifikansi tinggi.Kata kunci: Problem solving, keterampilan pemecahan masalah, siswa SMP